Development trends of the information technology and cyberspace security - Feng-hua LI (网络与信息安全学报)
The basic characteristics,mutual differences and intrinsic relationships of the internet,mobile internet,internet of things,cloud computing and big data technologies were analyzed,and the evolutions of the information technology and information service mode were deeply studied,the spiraling development trends of information technology and our catching up opportunities were explored,and that the major problem in next generation of in-formation technology was energy consumption was pointed out.Based on the analysis,the security requirements and challenges of the network connections,Industrie 4.0 issues in our cyberspace were analyzed,and that the research on security technology should be synchronized with the development of information technology was presented.Finally,the development opportunities and strategies of our cyberspace security were concluded,and an outlook of the de-velopment trends of the cyberspace security was given.